HUBUNGAN DUKUNGAN KELUARGA DENGAN KEPATUHAN DIET PASIEN DIABETES MELITUS TIPE II DIWILAYAH KERJA PUSKESMAS KURAITAJI KOTA PARIAMAN - ASMIATI, ASMIATI; NOER, SALMAN; SANTI, NOVITA (Sekolah Tinggi Ilmu Kesehatan (STIKes) Piala Sakti Pariaman, 2024)
Diabetes triggers 6.7 million deaths or 1 case every 5 seconds in sufferers. Indonesia is in fifth position for diabetes sufferers, namely 19.47 million. The study aims to determine the relationship between family support and dietary compliance of type 2 diabetes mellitus patients in the Kuraitaji Health Center Work Area, Pariaman City. This type of research is descriptive analytical with a cross-sectional approach design. The population in this study were 366 Type II DM sufferers. Sampling used a random sampling technique with a total of 65 people. Data collection was carried out by documentation study and computerized data processing, using univariate and bivariate analysis. The results of the univariate analysis showed that 47 respondents (60.3%) had insufficient family support, 8 respondents (10.3%) had sufficient family support, and 23 respondents (29.5%) had good family support. Type 2 DM sufferers who had non-compliance were 47 respondents (60.3%), and compliance was 31 respondents (39.7%). The results of the bivariate analysis showed a significant relationship between family support and dietary compliance in type II diabetes mellitus patients (p-value = 0.000 ≤ 0.05). In conclusion, family support is related to the level of compliance of patients with type 2 diabetes mellitus at the Kurai Taji Health Center, Pariaman City in 2022.